2021
DOI: 10.1590/s2175-97902020000419127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the applicative potential of pigments extracted from bacterial isolates of mangrove soil as topical UV protectants

Abstract: Antioxidant, antibacterial and UV protective activities of two pigments extracted from mangrove soil isolates were analysed for their applications as ingredients in sunscreen formulations. Through biochemical characterization, the isolates were tentatively identified as belonging to the Flavobacterium sp. and Brevibacterium sp. UV visible spectral characterization of the pigments indicated presence of carotenoids. The orange pigment exhibited Sun Protection factor (SPF) value of 5.3 while the yellow pigment SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Besides, the concentration of 10% (w/v) of carotenoids by Brevibacterium sp. has SPF value of 5.311 (Patki et al, 2021). Therefore, it is observed that SPF value increases as the pigment concentration increases.…”
Section: Potential As Sunscreen Agentmentioning
confidence: 92%
See 1 more Smart Citation
“…Besides, the concentration of 10% (w/v) of carotenoids by Brevibacterium sp. has SPF value of 5.311 (Patki et al, 2021). Therefore, it is observed that SPF value increases as the pigment concentration increases.…”
Section: Potential As Sunscreen Agentmentioning
confidence: 92%
“…There are several bacterial pigments that have potential as sunscreen agents because they have better survival with UV radiation (Patki et al, 2021). For instance, Suryawanshi et al (2015) stated that bacterial pigments such as violacein and prodigiosin can enhance the sun protection factor (SPF), which is a measurement of how well the UVB rays could be absorbed by a sunscreen product.…”
Section: Introductionmentioning
confidence: 99%
“…P1 produces a yellow pigment tentatively identified as zeaxanthin. The pigment extract at 5 mg/mL showed a broad range of antibacterial activity via the disk diffusion test, with haloes around 15 mm against S. aureus and E. coli [45]. Chryseobacterium strains present biosynthetic gene clusters responsible for the production of antimicrobials and may produce antibiotics [46].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Bacterial pigments like prodigiosin, violacein and melanin have been shown to be UV protective (Darshan & Manonmani, 2015; Kothari et al, 2017; Siezen, 2011; Patki et al, 2021). Many of them also have antimicrobial, antioxidant, anticancer, anti‐obesity and anti‐inflammatory properties which make them useful in the food, textiles, printing, pharmaceutical, and cosmetics industries (Revuelta & Vandamme, 2016; Sa'nchez‐Mun˜oz et al, 2020; Venil et al, 2020).…”
Section: Introductionmentioning
confidence: 99%